2014
DOI: 10.3109/07435800.2013.879169
|View full text |Cite
|
Sign up to set email alerts
|

The role of BRAF V600E mutation as a potential marker for prognostic stratification of papillary thyroid carcinoma: a long-term follow-up study

Abstract: Papillary carcinoma is the most prevalent malignancy of thyroid gland, and its incidence has been recently increased. The BRAF(V600E) mutation is the most frequent genetic alteration in papillary thyroid carcinoma (PTC). The role of BRAF(V600E) mutation as a potential prognostic factor has been controversially reported in different studies, with short-term follow-up. In this study, we evaluated the role of BRAF(V600E) mutation as a potential marker for prognostic stratification of patients with PTC in long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Daliri et al . (2014) analysed the relation between the BRAF V600E mutation and response to therapy in a fairly small group of 69 PTC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Daliri et al . (2014) analysed the relation between the BRAF V600E mutation and response to therapy in a fairly small group of 69 PTC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, patients exposed to Chernobyl radiation developed PTC, and survivors of the atomic bomb in Japan had a very high frequency of RET/PTC chromosomal rearrangement [36]. In addiction, B-Raf proto-oncogene (BRAF) mutation (BRAF V600E) was associated with PTC [37]. Guan et al [38] demonstrated that high iodine intake was a significant risk factor for BRAF V600E mutation and the development of PTC in the thyroid gland.…”
Section: Genes and Proteins Involved In Radiation-induced Cancermentioning
confidence: 99%
“…Synopsis of the main literature in the field [22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45]. HLA-DR: human leukocyte antigen-DR; RET/PTC : rearranged during transfection/papillary thyroid carcinoma; PKC: protein kinase C; MAPKK7: mitogen-activated protein kinase 7; JNK: c-Jun NH2-terminal kinases; IR: ionizing radiation; UV: ultraviolet rays; ROS: reactive oxygen species.…”
Section: Figurementioning
confidence: 99%
“…Most agents selective for these targets remain in early phases of development, but inhibitors directed at several specific targets are reaching maturity [1012]. The BRAF V600E mutation, which is present in a significant proportion of cases of PTC [62], is the target of the small molecule inhibitors vemurafenib and dabrafenib [3941], which are both agents approved by the FDA for treatment of advanced melanoma harboring this mutation [20]. …”
Section: Additional Targets and Strategies In Late-stage Developmentmentioning
confidence: 99%